Ngoma: approaches to arts education in Southern Africa: by Robert Mshengu Kavanagh and Stephen Chifunyise, CreateSpace Independent Publishing Platform, pp. 168, $9.99 (Paperback), ISBN-13: 978-1517490362. - Mkaronda, Nicholas (South African Theatre Journal (Taylor & Francis Ltd ), 2023)
The article discusses the book "Ngoma: Approaches to Arts Education in Southern Africa," which compiles insights from various contributors on the state of arts education in Southern Africa, particularly in the context of post-colonial challenges. The authors emphasize the need for arts education that reflects the cultures of the majority indigenous populations, contrasting it with the colonial education system that favored Western art forms and marginalized local traditions. The book critiques the role of formal education systems and advocates for the involvement of non-state actors in promoting arts education, highlighting the ongoing struggle for cultural identity and the decolonization of education in the region. It serves as a resource for arts educators and education planners, addressing historical contexts and proposing models for future arts education initiatives.